Dopaminergic Control of Striatal Cholinergic Interneurons Underlies Cocaine-Induced Psychostimulation - Lewis, Robert G.; Serra, Marcello; Radl, Daniela; Gori, Michela; Tran, Catherine; Michalak, Sharon E.; Vanderwal, Christopher D.; Borrelli, Emiliana (Cell reports (Cambridge), 2020)
Cocaine drastically elevates dopamine (DA) levels in the striatum, a brain region that is critical to the psychomotor and rewarding properties of the drug. DA signaling regulates intrastriatal circuits connecting medium spiny neurons (MSNs) with afferent fibers and interneurons. While the cocaine-mediated increase in DA signaling on MSNs is well documented, that on cholinergic interneurons (ChIs) has been more difficult to assess. Using combined pharmacological, chemogenetic, and cell-specific ablation approaches, we reveal that the D2R-dependent inhibition of acetylcholine (ACh) signaling is fundamental to cocaine-induced changes in behavior and the striatal genomic response. We show that the D2R-dependent control of striatal ChIs enables the motor, sensitized, and reinforcing properties of cocaine. This study highlights the importance of the DA- and D2R-mediated inhibitory control of ChIs activity in the normal functioning of striatal networks. [Display omitted] •D2R signaling in ChIs enables the motor and cellular effects of cocaine in male mice•Absence of D2R in ChIs increases cocaine-dependent striatal ACh signaling•M4R overactivation in striatal circuits prevents the full response to cocaine•The reinforcing effects of cocaine are abolished in the absence of D2R in ChIs Cocaine increases striatal dopamine, which is responsible for the psychomotor effects of the drug. Lewis et al. analyze how alterations of D2R signaling in cholinergic interneurons affect cocaine-mediated responses and show that the absence of D2R reduces the motor response to the drug and abolishes its reinforcing properties.